Assessment of Soil Organic Matter and Its Microbial Role in Selected Locations in the South Bohemia Region (Czech Republic) - David Kabelka; Petr Konvalina; Marek Kopecký; Eva Klenotová; Jaroslav Šíma (Land)
Organic matter has a very important function in soil, without which, soil formation processes cannot take place properly. It can be divided and classified based on several aspects; the most general division is between the living and non-living parts of organic matter. The results presented in this paper specifically refer to the living microbial part of organic matter. This research was carried out in the years 2021–2024 in the South Bohemia region located in the Czech Republic. Two types of land use (four permanent grassland areas, two forest areas) were evaluated. Based on laboratory soil analyses, some significant dependencies were found. For example, in grasslands with statistically identical pH, there was a dependence (p-value 0.05) between soil organic carbon (SOC), carbon of microbial biomass (MBC) and microbial basal respiration (MBR). Additionally, coniferous forest experimental locations had a lower pH, which, in turn, slowed the activity of microorganisms and promoted the accumulation of SOC in the soil. The results from this experiment support the current knowledge of organic matter and are important for a better understanding of the soil organic matter cycle.